A adaptação dos estudantes universitários estrangeiros no Brasil em face da internacionalização do ensino superior: uma revisão de escopo - Zembrzuski, Letícia Janaina Possa (2021)
This study addresses the adaptation of foreign university students in Brazil within the perspective of the internationalization of Higher Education and was motivated by the need to understand the reality of these students who seek training outside their country of origin. An attempt was made to analyze the advances on the subject in recent years, which need to be clarified through analyzes that lead to measures of theoretical and empirical frameworks established to understand student flows and the facilitating and hindering factors involved. Thus, the research aimed to analyze the adaptation process of foreign university students in Brazilian universities. The method adopted was the scope review, which included the use of searches in online bibliographic databases of publications between 2009 and 2019, using as a guiding question: "What factors affect the adaptation of foreign immigrant undergraduate students when seeking a university education in Brazil? ”. As a result of the research, 11 studies that met the inclusion criteria were selected. These studies showed that there are facilitating elements, such as the network of friendships and social relationships, student assistance, language and cultural and affective aspects, but there are also difficulties in adaptation related to the difficulties of daily life (adaptation of food, housing, health, cost of life, climate and safety). On the other hand, there are also social and emotional difficulties represented by the prejudice and discrimination they suffer, the family absence that leads to psychological distress, at the same time it is clear that public policies for reception and student assistance at universities need to be improved, to act in the reduction of dropouts in universities.